STUDY OF LITERATURE RELATED TO STAFF PERFORMANCE FACTORS' LINKAGES TO INCOMPLETE MEDICAL RECORD DOCUMENTS IN PUBLIC HEALTH CENTER - Wijayanti, Rossalina Adi; Zatin, Widian Almas; Nuraini, Novita (Journal of Public Health Research and Community Health Development, 2023)
ABSTRACT Background:  Excellent and quality medical record services can be seen from the contents of the completeness of the file, timely, accurate and compliance with aspects of legal requirements.  The ideal standard for the completeness of medical record documents is 100%. However, based on a literature review, there are still medical record documents which weren't 100% complete. The incomplete filling of medical record documents is related to many things, including the delay in fulfilling the patient's rights to the contents of the medical record and reduction in the quality of medical record services. Purpose:  The study aims to analyze the factors causing the incomplete filling of medical record documents at the  public health center. Method:  Data collection was conducted by literature search from the Google Scholar database and the Garuda Portal, and 12 articles were reviewed. Result: The biggest factor identified was the individual factors, namely the skills factor (75%), then knowledge factor (50%), and the lowest percentage was the ability factor (16.67%). On the organizational and motivator variables, the identified factors were leadership (50%) and motivator (16.67%). Conclusion: There was a need for documentation procedures in the form of Standard Operating Procedure that were socialized to health workers.  There is also a need for leaders to provide communication forum between health personnels, and a form of evaluation and control in good and correct documentation of medical records combined with rewards and punishment system. It is also necessary to provide seminars and trainings to health workers regarding correct medical record filling. Health workers who have limited time to fill out, can arrange a good work plan.